PENERAPAN PROGRAM KAMPUNGE AREK SUROBOYO (KASRPA) KAMPUNG BELAJAR DI KELURAHAN MEDOKAN SEMAMPIR - Fadhlan Firdaus Syafrudin; Oktarizka Reviandani (Journal Publicuho, 2023)
The research aims to determine the process of implementing the Kampung Arek Suroboyo (KAS RPA) program in Medokan Semampir Village. This research adopts a qualitative method that uses a descriptive approach. Data collection was carried out by conducting interviews, field visits, and collecting documentation. The focus of this research is to look at the implementation process, namely policy standards and targets, resources, characteristics of implementing organizations, communication between related organizations and implementation activities, attitudes of implementers and the social environment. The results of the research show that the implementation of the learning village program in Medokan Semampir Subdistrict has been effective, but there is one indicator that has not been met, namely the indicator of a social environment that is not supportive because one of the programs of the learning village, namely the reading park, is less popular because the operating hours are not in sync with school schedules, small book collections, and children's low interest in reading.